Assessment of the performance of timekeepers for swimming competitions - Godolphin, J. D.; Faux, D. A. (Journal of Swimming Research, 2020)
n swimming competitions, race times are generally measured using full electronic timing with back-up times provided by semi-manual and manual (stopwatch) timing. The official race time is taken to be the electronic time. However, the reliability of the semi-manual and manual times are important in determining swimmer performance, since either can be used as the official race time, for example, if the electronic time is missing. National swimming governing bodies oversee the training of officials. Timekeeper training includes a practical assessment of performance at manual timekeeping conducted at the poolside. No consistent test criterion is applied to this practical assessment due to the absence of robust reaction time data upon which to base a test. The recent publication of a substantial data set of timekeeper reaction times has allowed the timing characteristics of trained timekeepers to be described by means of a timing profile. Consideration of timekeeper candidates with timing profiles consistent with that of a trained timekeeper and of candidates with significantly different timing profiles enables the properties of practical timekeeping tests to be evaluated. Two tests with good properties are proposed to assess perfor mance at manual timekeeping. Further, a test to assess performance at semi-manual timekeeping is proposed. This is an aspect of timekeeping which has no practical assessment under the current training regime.